2009
DOI: 10.1007/s11465-009-0031-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between four piezoelectric energy harvesting circuits

Abstract: This paper investigates and compares the efficiencies of four different interfaces for vibrationbased energy harvesting systems. Among those four circuits, two circuits adopt the synchronous switching technique, in which the circuit is switched synchronously with the vibration. In this study, a simple source-less trigger circuit used to control the synchronized switch is proposed and two interface circuits of energy harvesting systems are designed based on the trigger circuit. To validate the effectiveness of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 10 publications
0
52
0
Order By: Relevance
“…This solution for inverting the voltage across the piezoelectric element requires very low power as it does not need any external energy, except to control the digital switch. This autonomous voltage inverter can therefore be made self-powered [21,26,27,[32][33][34][35][36][37][38], consuming a very small amount of power (typically 3% of the electrostatic energy available on the active material); as will be discussed in Section 4.2. As the energy conversion gain is typically in the range of a factor of 20, this energy requirement can easily be neglected.…”
Section: Switching Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…This solution for inverting the voltage across the piezoelectric element requires very low power as it does not need any external energy, except to control the digital switch. This autonomous voltage inverter can therefore be made self-powered [21,26,27,[32][33][34][35][36][37][38], consuming a very small amount of power (typically 3% of the electrostatic energy available on the active material); as will be discussed in Section 4.2. As the energy conversion gain is typically in the range of a factor of 20, this energy requirement can easily be neglected.…”
Section: Switching Techniquesmentioning
confidence: 99%
“…The purpose of the present study is to provide an up-to-date view of such systems. In this field, Guyomar et al introduced a simple, low-cost process to artificially enhance the coupling coefficient of electromechanical systems using piezomaterials [17][18][19][20][21][22]. Based on a simple nonlinear process of the output voltage of the active material, this approach, initially developed for vibration damping purposes [23][24][25][26][27], permits a gain of up to 20 in terms of energy conversion, and 10 in terms of harvested energy [28].…”
Section: Introductionmentioning
confidence: 99%
“…Now the basic principles of the nonlinear conversion enhancement exposed, this section proposes the direct application of this concept to energy harvesting, leading to the concept of Synchronized Switch Harvesting on Inductor Lefeuvre et al, 2006a;Shu, Lien and Wu, 2007;Liang and Liao, 2009;Qiu et al, 2009b). Considering the standard energy harvesting interface that consists in connecting the piezoelectric element to a smoothing capacitor C S and load R L (that represents the connected device) through a diode bridge rectifier (Figure 4(a)), the switching element may be placed in two ways: When using the standard interface, it can be demonstrated that the harvested energy under a constant vibration magnitude u M is given in steady state case by : …”
Section: Ssh Techniquesmentioning
confidence: 99%
“…However, single crystals are difficult to obtain, and no industrial process has been achieved, compromising the design of low-cost microgenerators using such materials. In order to enhance the harvesting abilities, a nonlinear approach has been proposed that allows an artificial increase of the global electromechanical coupling coefficient Lefeuvre et al, 2006;Makihara, Onoda and Miyakawa, 2006;Qiu et al, 2009;Shu, Lien and Wu, 2007). This process consists of quickly inverting the piezoelectric voltage when the displacement or temperature reaches a maximum or a minimum value (or equivalently when the velocity cancels), as shown in Figure 4.…”
Section: Conversion Improvementmentioning
confidence: 99%
“…Actually, the minimum and maximum detection can be done by comparing the voltage across the active material with its delayed version. The maximum is then detected when the delayed signal is greater than the original one (Lallart et al, 2008b;Liang and Liao, 2009;Qiu et al, 2009;. The self-powered autonomous switching device based on this principles therefore consumes very little power, typically less than 5% than the electrostatic energy available on the ferroelectric material, therefore not compromising the energy harvesting gain.…”
Section: Implementation Considerationsmentioning
confidence: 99%